The Crosstalk Between Long Non-Coding RNAs and Various Types of Death in Cancer Cells. (16th July 2021) - Tang, Wenwen; Zhu, Shaomi; Liang, Xin; Liu, Chi; Song, Linjiang
With the increasing aging population, cancer has become one of the leading causes of death worldwide, and the number of cancer cases and deaths is only anticipated to grow further. Long non-coding RNAs (lncRNAs), which are closely associated with the expression level of downstream genes and various types of bioactivity, are regarded as one of the key regulators of cancer cell proliferation and death. Cell death, including apoptosis, necrosis, autophagy, pyroptosis, and ferroptosis, plays a vital role in the progression of cancer. A better understanding of the regulatory relationships between lncRNAs and these various types of cancer cell death is therefore urgently required. The occurrence and development of tumors can be controlled by increasing or decreasing the expression of lncRNAs, a method which confers broad prospects for cancer treatment. Therefore, it is urgent for us to understand the influence of lncRNAs on the development of different modes of tumor death, and to evaluate whether lncRNAs have the potential to be used as biological targets for inducing cell death and predicting prognosis and recurrence of chemotherapy. The purpose of this review is to provide an overview of the various forms of cancer cell death, including apoptosis, necrosis, autophagy, pyroptosis, and ferroptosis, and to describe the mechanisms of different types of cancer cell death that are regulated by lncRNAs in order to explore potential targets for cancer therapy.